Boundary layer flow over elastic surfaces and combined method of drag reduction - Babenko, Viktor V.; Chun, Ho Hwan; Lee, Inwon (Elsevier, 2012)
While other methods of drag reduction are well-known in marine R & D and ship design environments worldwide, compliant coating drag reduction remains less well-known and poorly understood. This book presents cutting-edge techniques and findings from research sources not generally accessible by Western researchers and engineers, aiding the application and further development of this potentially important technology.